DIRECT INVESTMENTS IN SPA TOURISM OF UNDEVELOPED RURAL REGIONS: CASE STUDY OF THE МUNICIPALITY OF KURŠUMLIJA - Ljubisavljević, Tijana; Gnjatović, Dragana (Economics of Agriculture, 2020)
In this paper we analyze the role of direct investments in spa tourism in undeveloped rural regions on the example of the Municipality of Kuršumlija. Namely, the Municipality of Kuršumlija belongs to the group of undeveloped regions. On its territory, three spa resorts are located. In order to explore the role of direct investments in the development of these spa resorts, qualitative survey was conducted using the technique of semi-structured in-depth interviews with the representatives of relevant institutions and organizations in the Municipality of Kuršumlija. Obtained results showed that the completion of the privatization process of the spa facilities along with the use of investment incentives and creation of favorable business environment for investors would lead to the increase of direct investments aimed for the development of the spa resorts. Direct investments, through better utilization of natural healing factors and human resources, would create the conditions for the development of health tourism and thus would lead to the development of the undeveloped rural area where the spa complex is located.